H.E.S.S. discovery of very high energy γ-ray emission from PKS 0625-354 - Abdalla, Hassan; Cologna, Gabriele; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Wagner, Stefan; Hofmann, Werner (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. PKS 0625−354 (z = 0.055) was observed with the four High Energy Stereoscopic System (H.E.S.S.) telescopes in 2012 during 5.5 h. The source was detect